Intra-household labor allocation in colonial Nigeria - Arthi, V; Fenske, J (Elsevier, 2015)
We use a year-long panel of time-use data from colonial Nigeria to show that labor complementarities and strategic concerns shaped the time-use decisions of African households. Using quantitative and ethnographic approaches, we show that health shocks imposed time costs that followed the gender division of labor. The labor of others did not automatically compensate for this. Whether individuals could respond by recruiting substitutes depended on social standing, urgency of work, and type of illness. Labor was coordinated between spouses. Child labor was coordinated with parental work, aided child care, and allowed children to build skills and resources.